Desmoplastic ameloblastoma: A case report - Shruthi K Patil; Neethu Telagi; Mukund R Nair; B R Ahmed Mujib (Journal of Family Medicine and Primary Care, 2020)
Desmoplastic ameloblastoma (DA) is a rare variant of ameloblastoma, accounting for approximately 4 to 13% of ameloblastomas. It is uncommon, aggressive in nature, and there are high chances of misdiagnosis. Clinical and radiographical features are similar to fibro-osseous lesions of jaw. We reported a case of 35-year-old male patient of DA.